Effect of Oral Supplementation of the Linoleic and Gammalinolenic Acids on the Diabetic Pregnant Rats - Consonni, Marcos [UNESP]; Damasceno, Débora Cristina [UNESP]; Kempinas, Wilma de Grava [UNESP]; Nassr, Azize Cristina Capelli [UNESP]; Volpato, Gustavo Tadeu [UNESP]; Dallaqua, Bruna [UNESP]; Iessi, Isabela Lovizutto [UNESP]; Saito, Felipe Hiroshi [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Inst Tecnologia Parana, 2012)
The aim of this work was to evaluate the direct protective action of oral fatty acid supplementation against the deleterious effect of hyperglycemia on maternal reproductive outcomes; fetal growth and development on female Wistar rats. The animals were distributed into four experimental groups: G1= non-diabetic without supplementation (Control group); G2= non-diabetic treated with linoleic (LA) and gammalinolenic acid (GLA) (1 mL of Gamaline-V/day); G3= diabetic without supplementation and G4= diabetic treated with LA and GLA. Diabetes was induced by streptozotocin (40 mg/kg). At day 21 of pregnancy, the gravid uterus was weighed and dissected to count the dead and live fetuses, resorption, implantation, and corpora lutea numbers. The fetuses were analyzed for external and internal anomalies. The treatment with Gamaline-V supplementation to diabetic rats interfered in the maternal reproductive outcome (reduced number of live fetuses and embryonic implantation); however, it protected the deleterious on the incidence of congenital anomalies caused by hyperglycemia.
Keywords: diabetes; rat; pregnancy; anomalies; fatty acid supplementation; Gamaline-V